1959
DOI: 10.1115/1.4008316
|View full text |Cite
|
Sign up to set email alerts
|

Some Observations on the Shearing Process in Metal Cutting

Abstract: It was found that shearing forces on the shear plane were linear functions of the area on which they acted. This was observed for all materials investigated; for SAE 1112 steel, 2024-T4, and 6061-T6 aluminum alloys, and alpha-brass, and also is in agreement with data taken from the literature. Furthermore, all data examined showed that the straight line of shear force Fs versus area As intercepted the ordinate at a positive force value. This was interpreted to mean that the intercept part of the shearing force… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 0 publications
0
23
0
Order By: Relevance
“…Similar conclusions have been arrived at in prior studies using quick-stop and related observations. [12,13] Furthermore, the PIV analysis has shown that the cumulative strain imposed in the chip varies for different materials at the same tool rake angle. These observations highlight the need for modeling of the chip formation process to relate machining parameters (e.g., rake angle, velocity, and friction) to deformation parameters (e.g., strain, strain rate, and temperature) ( Figure 1).…”
Section: B Experimental Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar conclusions have been arrived at in prior studies using quick-stop and related observations. [12,13] Furthermore, the PIV analysis has shown that the cumulative strain imposed in the chip varies for different materials at the same tool rake angle. These observations highlight the need for modeling of the chip formation process to relate machining parameters (e.g., rake angle, velocity, and friction) to deformation parameters (e.g., strain, strain rate, and temperature) ( Figure 1).…”
Section: B Experimental Resultsmentioning
confidence: 99%
“…[11][12][13] Although the chip length increases proportional to the length of cut, the deformed chip thickness, precut (undeformed) thickness, and cutting velocity all remain constant after deformation has reached steady state. Therefore the deformation zone should maintain a constant size and shape after a certain amount of incipient deformation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[5] Chip formation occurs by concentrated shear within a narrow, primary deformation zone often idealized as the ''shear plane.'' [5,6,7] The microstructure changes associated with the formation of UFG chips have been attributed to the large shear strains imposed within this deformation zone. [8] In the shear plane model of plane-strain machining, the deformation field is uniquely determined by the tool rake angle (a) and the shear angle (f).…”
Section: Introductionmentioning
confidence: 99%
“…In practice, the primary deformation zone is not a plane but a fan-shaped zone of finite width and thickness, [6,7] and the shear strain within this zone may or may not be uniform over its volume. While the deformation field in this zone has been the subject of intensive numerical study using theoretical or computational analysis, [10,11,12] there have been few experimental determinations of the strain distribution in and around this zone.…”
Section: Introductionmentioning
confidence: 99%